Determinación de aflatoxina total y ocratoxina a en maca seca y en harina de maca - Reyes D., Vilma J. (2006)
It has been determined the concentration of total aflatoxin and A ochratoxín in dried maca (Lepidium meyenii walp) and maca flour and the physicochemical and microbiological factors affecting their production. It has been collected samples from 4 productive communitíes and 4 main markets. Extrinsic factors such as temperature and relative humidity are 10°C y 52,5% in communities and 15 °C y 71% in markets which are favourable conditions for growing Fusarium avenaceum, Penicillium corylophylum, P.commune, P.chrysogenum, Aspergi1us níger, A. flavus, A.ochraceus, esclerotia, A. flavus, Rizophus and yeasts. It was also determined total aflatoxin content average (0,829 mg/kg), which indicates the good quality of dried maca and A ochratoxin content average (8,703 ppb), which exceeds the permissible maximum limit given by USL 123/2005. The factors affecting A ocratoxin production are reducing sugars and pH. Total fungi average is 50x102 cfu/g but is not a factor affecting this mycotoxin. The community samples had higher concentrations of A ochratoxin and total fungi than the market samples. In maca flour, total aflatoxin content average is 12.4528 ppb in which the toasted flour in bulk from the Central market in Lima had the highest content and the main influential factors are humidity, pH and acidity, whíle A ochratoxin content average is 2.8916ppb, in which the flour from Chupaca had the highest concentration and the main influential factors are reducing sugars and pH. On the other hand, the number of fungi in maca flour is 78 x 102 cfu/g affecting total Aflatoxin but not A ocratoxin production.